Reproductive biology of Dactylopterus volitans (Teleostei: Dactylopteridae), from the northern coast of São Paulo State, Brazil - Machado, Janaina F.; Zambeli, Raquel M.; Vianna, Marcelo (Arquivos de Ciências do Mar, 2017)
The pink shrimp fisheries in Southeast Brazil are not directed only to that resource, causing an impact on stocks of several species, including Dactylopterus volitans. In this paper, data on its reproductive biology were analyzed by means of 592 specimens caught on the northern coast of São Paulo State, Brazil from July, 1995 through August, 1996. Individuals measuring from 7.0 to 35.5 cm TL were recorded, with main modal value of 10.0 cm TL. The biometric relationships “standard length(SL/total length (TL)” and “total weight (TW)/total length (TL)” were given by equations: SL = 0.8276 LT – 01746 and TW = 0.0072 LT3.097. The L50 values for females, males and both sexes were 17.38 cm, 19.25 cm and 18.09 cm, respectively. An increase of gonad weight was recorded on the period from November to February, which should correspond with the spawning season. The estimates of L50´ modal length and reproductive season indicate that a high share of juvenile individuals occur in the catch and that the closed season of pink shrimp does not preserve the reproductive stock of D. volitans, what highlights the great impact caused by the shrimp fishery on its stock.